(untitled) (Comprehensive Journal of Science, 2025)
: Recently, there has been a significant desire among national enterprises to rely on key performance indicators as a tool to measure performance and the achieved goals through official decisions and reports of government agencies. Therefore, there has been an urgent need to conduct studies that focus on measuring knowledge of these indicators and the degree of their application, if any, to provide realistic data in preparation for developing or formulating various performance indicators for all these enterprises. Locally, the subject has not been adequately studied, and the few and limited researches locally have addressed the indicators in terms of defining them, the importance, and the possibility of their application, while they have not addressed the knowledge level of the national enterprises’ management’s. The main objective of this research is to "Evaluating the national enterprises departments knowledge about the key performance indexes". This research adopted the descriptive analytical methodology by studying the case of the local investment sector. The study sample consisted of employees of senior management and owners in national investment enterprises. The statistical population study was (136) employees. The necessary data were collected through a questionnaire tool, where (101) questionnaires were distributed to the study Sample space. The recovery rate was (71%) and the results of the Cronbach's alpha test for the study were (0.806). The overall Spearman reliability coefficient was (0.693). Direct observation and review of archival records were also relied upon. The design of the robust questionnaire relied on the principles and rules of the taxonomy and Norman Webb scale for measuring learning, in addition to the various dimensions of balanced score card. Computer applications and the statistical package program SPSS were used to analyze and interpret the collected data. This research resulted in several findings, including: the knowledge level of  key performance indicators and the extent of their use among the study sample does not meet the knowledge needs of investment enterprises. Employees had misconceptions that applying the indicators is a threat to their jobs because they are unfair standards compared to the education and training they have received. However, limited resistance to change was observed in misunderstanding and comprehension of the nature of these indicators. The research showed in the recommendation the urgent need to formulate key performance indicators and generalize them to the rest of the sectors to launch a national project for key performance indicators that can be applied in the local work environment
Keywords: : KPIs; National enterprises; Evaluating the knowledge; Bloom's Taxonomy; Norman Webb scales; Balance Scorecard.